Linkage of SSR markers with rice blast resistance and development of partial resistant advanced lines of rice (Oryza sativa) through marker-assisted selection - Abdul Latif, Mohammad; Hasan, Mohammad Kamrul; Kabir, Amirul; Hasan, Md. Al-Imran; Bhuiyan, Md. Rejwan; Yusop, Mohd Rafii; Abdul Latif, Mohammad (Springer, 2022)
Rice blast disease is one of the major bottlenecks of rice production in the world including Bangladesh. To develop blast resistant lines, a cross was made between a high yielding but blast susceptible variety MR263 and a blast resistant variety Pongsu seribu 2. Marker-assisted backcross breeding was followed to develop F1, BC1F1, BC2F1, BC2F2, BC2F3, BC2F4 and BC2F5 population. DNA markers i.e., RM206, RM1359 and RM8225 closely linked to Pb1, pi21 and Piz blast resistant genes, respectively and marker RM276 linked to panicle blast resistant QTL (qPbj-6.1) were used in foreground selection. Calculated chi-square (χ2) value of phenotypic and genotypic segregation data of BC2F1 population followed goodness of fit to the expected ratio (1:1) (phenotypic data χ2 = 1.08, p = 0.701; genotypic data χ2 = range from 0.33 to 3.00, p = 0.08–0.56) and it indicates that the inheritance pattern of blast resistance was followed by a single gene model. Eighty-nine advanced lines of BC2F5 population were developed and out of them, 58 lines contained Piz, Pb1, pi21, and qPbj-6.1 while 31 lines contained Piz, Pb1, and QTL qPbj-6.1. Marker-trait association analysis revealed that molecular markers i.e., RM206, RM276, and RM8225 were tightly linked with blast resistance, and each marker was explained by 33.33% phenotypic variation (resistance reaction). Morphological and pathogenicity performance of advanced lines was better compared to the recurrent parent. Developed blast resistance advanced lines could be used as donors or blast resistant variety for the management of devastating rice blast disease.